AT asked in Science & MathematicsMathematics · 1 decade ago

yet another completing the square problem !!?

3x^2-9x=0

complete the square.

explain & list out steps please.

6 Answers

Relevance
  • Anonymous
    1 decade ago
    Favorite Answer

    Same process as the last one. To complete a square:

    [1] Divide the equation by the coefficient of the x² term.

    [2] "Half going down, square going up."

    [3] Take the square root of both sides and solve for x.

    3x² - 9x = 0 [Divide everything by 3.]

    x² - 3x = 0 [Rewrite with blanks, then fill them in. "Half going down, square going up."]

    x² - 3x + ___ = 0 + ___

    (x + ___)² = 0 + ___

    Half of -3 is -3/2. This goes on the blank inside the parentheses.

    (-3/2)² = 9/4. This goes on the blank above the parentheses (and to the ones on the right side of the equation). Now solve for x.

    x² - 3x + 9/4 = 0 + 9/4

    (x - 3/2)² = 9/4

    √(x - 3/2)² = √(9/4)

    |x - 3/2| = 3/2

    x - 3/2 = ±3/2

    x = 3/2 ± 3/2

    x = 6/2 = 3 or x = 0/2 = 0.

    x = 3 or x = 0.

  • Anonymous
    1 decade ago

    1) Divide out a "3":

    3(x^2 - 3x) = 0

    2) Take the "-3x" term and divide the coefficient by 2

    -3 / 2 = -3/2

    3) Find the square of -3/2

    (-3/2)^2 = 9/4

    4) You've found the number to add to (x^2 - 3x) to get a perfect square trinomial, so add it to the terms:

    3(x^2 - 3x + 9/4)

    5) Since you've added it to one side of the equation, add it to the other. But, since it is in the parentheses, multiply it by the "3" outside of the parentheses first:

    3(x^2 - 3x + 9/4) = 3*9/4

    6) Write the trinomial as the square of a binomial:

    3 (x - (3/2))^2 = 27/4

    (x - (3/2))^2 = 9/4

    7)Take square roots of each side and solve(remember if you take a square root, the answer is either negative or positive):

    x - (3/2) = +/-3/2

    x = 0 or 3

  • 1 decade ago

    To complete the square of the equation 3x^2 - 9x = 0

    or it is x^2 - 3x = 0

    You have to take the coefficient of x and divide by 2 and square and add and substract this number, you will complete the square.

    In this example, the coefficient of x is 3 and divide by 2 it becomes 3/2 and by squaring you get 9/4

    Now, x^2 - 3x = 0, becomes x^2 - 3x + 9/4 = 9/4

    or (x - 3/2)^2 = 9/4

  • 1 decade ago

    3x^2 - 9x = 0

    divide everything by 3

    x^2 - 3x = 0

    find half of 3, square it, add to both sides

    x^2 - 3x + (9/4) = (9/4)

    factor left side into a perfect square

    (x - (3/2))^2 = (9/4)

    sqrt both sides

    x - (3/2) = ±(3/2)

    x = (3/2) ± (3/2)

    x = 0 or (6/2)

    x = 0 or 3

    ANS : 0 or 3

  • How do you think about the answers? You can sign in to vote the answer.
  • 4 years ago

    Assuming the pawn strikes in a random 14 bypass progression, i'd commence off with the equation P(ok)=a million-(13k/sixty 2) in the initiating, the 13 as a results of kind of places the pawn will bypass that are at probability of a capture. This excludes the taking off and ending factor. ok/sixty 2 is the threat that a random spot on the board is trapped, sixty 2 being the kind of spots on the board a capture may be positioned (8*8-2) //word - this assumes a niche may be trapped diverse situations, a mild adjustment may fix this I multiply the 13 in because besides the actuality that if one spot is trapped, the pawn fails. finally, I subtract it from a million because (13k/sixty 2) is the threat that the pawn receives trapped. i do not comprehend the position to truly bypass from the following, yet desire it enables.

  • 1 decade ago

    3x^2 - 9x = 0

    3x^2 = 9X

    X^2 = 3x

    x^2 - 3x = 0

    x (x - 3) = 0

    x = 0, or x = 3

    You can double check the answers by plugging each value of X back into your original equation.

Still have questions? Get your answers by asking now.